2011
DOI: 10.1007/s10895-011-0991-3
|View full text |Cite
|
Sign up to set email alerts
|

FITC Labeled Silica Nanoparticles as Efficient Cell Tags: Uptake and Photostability Study in Endothelial Cells

Abstract: The use of fluorescent nanomaterials has gained great importance in the field of medical imaging. Many traditional imaging technologies have been reported utilizing dyes in the past. These methods face drawbacks due to non-specific accumulation and photobleaching of dyes. We studied the uptake and internalization of two different sized (30 nm and 100 nm) FITC labeled silica nanoparticles in Human umbilical vein endothelial cell line. These nanomaterials show high biocompatability and are highly photostable ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…b Cell lines treated with non-targeted Si-PTX NPs-all cell lines were dead proving non-specificity of nanomaterials devoid of targeting scheme. c Cell lines treated with Apt-Si-PTX NPsnormal L929 cells were spared and cancer cell lines were 90% dead microscopy showed the internalization of Si-FITC nanoparticles by both the plants cells as well as animal cells in our previous reports [13,14]. Our earlier report showed that 2 h incubation was quite enough for internalization of silica nanoparticles inside live cells.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…b Cell lines treated with non-targeted Si-PTX NPs-all cell lines were dead proving non-specificity of nanomaterials devoid of targeting scheme. c Cell lines treated with Apt-Si-PTX NPsnormal L929 cells were spared and cancer cell lines were 90% dead microscopy showed the internalization of Si-FITC nanoparticles by both the plants cells as well as animal cells in our previous reports [13,14]. Our earlier report showed that 2 h incubation was quite enough for internalization of silica nanoparticles inside live cells.…”
Section: Resultsmentioning
confidence: 80%
“…Silica nanoparticles were prepared using template-directed synthesis method that has been reported elsewhere [14]. CTAB was used as template for pore formation, TEOS as silica source, ammonia as catalyst along with ethanol, and dd.H 2 O as solvent.…”
Section: Preparation Of Porous Silicamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, silica is an inert layer that confers water solubility and shields the optical property of the core. [34][35][36][37][38] Cadmium selenide and cadmium telluride QDs have been widely synthesized and studied as cyto-labels. [39][40][41] Cadmium sulfide (CdS) QDs have, as of yet, not created their own niche in the area of biological imaging due to their weak emissions in comparison with their selenide and telluride counterparts.…”
Section: Preparation Of Bare Cds and Silica-coated Cdsmentioning
confidence: 99%
“…Cancer nanotechnology has become a well researched interdisciplinary field enabling fabrication of nanotools to yield high image contrast, sensitivity and specificity [5][6][7]. Recent research has witnessed wide range of fluorescent nanomaterials applied for biological imaging [8]. Fluorescent markers at single molecular level are the need of the hour in particular for imaging molecular events inside live cells, such as signaling pathways for the study of cellular metabolism [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%